Analysis of the Effect of Climate Change on Public Health in Coastal Areas in Lapulu Village, Abeli Subdistrict, Kendari City in 2024 - Devi Savitri Effendy; Seltiona Tiku Rara; Sitti Amalia Nur; Sesy Dwi Prinita Jafarudin; Salwa Safitra; Siti Rahmawati; Setriyalin Putri Amir; Risti (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Abstract Background: Climate change represents one of the most pressing global challenges of the present era. Anthropogenic activities, particularly the emission of greenhouse gases such as carbon dioxide (CO₂) and methane (CH₄), have significantly contributed to alterations in global weather and climate patterns. These climatic changes have direct and indirect implications for human health, including increased risks of disease outbreaks. Extreme and unpredictable climate conditions can lead to a higher incidence of illnesses such as dengue fever, skin diseases, and respiratory infections (e.g., coughs and colds). Methods: This study employed a descriptive observational approach with a cross-sectional design. The research was conducted in the coastal area of Lapulu Village, Abeli Subdistrict, Kendari City, from late November to early December 2024. The target population consisted of residents living in the coastal area of Lapulu Village, with a total sample of 370 individuals selected for participation. Results: The analysis revealed no statistically significant relationship between climate change and the incidence of illness (p = 0.301), quality of drinking water (p = 0.875), access to health services (p = 0.746), or household income (p = 0.058). All p-values exceeded the significance threshold of 0.05, indicating that climate change was not significantly associated with these variables among residents of Lapulu Village. Conclusion: The findings from this study suggest that climate change does not have a statistically significant relationship with the incidence of illness, access to health services, quality of drinking water, or household income in the coastal area of Lapulu Village, Abeli Subdistrict, Kendari City. Despite the absence of significant associations, ongoing monitoring and further research are essential to better understand the long-term impacts of climate change on public health and socio-economic conditions in coastal communities. Keywords: Climate Change, Human Health, Access to Health Services, Disease Outbreaks, Dengue, Coastal Communities